Moderate Prenatal Alcohol Exposure Impairs Visual‐Spatial Discrimination in a Sex‐Specific Manner: Effects of Testing Order and Difficulty on Learning Performance. (6th September 2020) - Kenton, Johnny A.; Castillo, Victoria K.; Kehrer, Penelope E.; Brigman, Jonathan L.
Abstract : Background: Exposure to high levels of alcohol during development leads to alterations in neurogenesis and deficits in hippocampal‐dependent learning. Evidence suggests that even more moderate alcohol consumption during pregnancy can have negative impacts on the cognitive function of offspring. Methods for assessing impairments differ greatly across species, complicating translation of preclinical findings into potential therapeutics. We have demonstrated the utility of a touchscreen operant measure for assessing hippocampal function in mice. Methods: Here, we integrated a well‐established "drinking‐in‐the‐dark" exposure model that produces reliable, but more moderate, levels of maternal intoxication with a trial‐unique, delayed nonmatching‐to‐location (TUNL) task to examine the effects of prenatal alcohol exposure (PAE) on hippocampal‐sensitive behavior directly analogous to those used in clinical assessment. PAE and SAC offspring mice were trained to touch a single visual stimulus ("sample phase") in one of 10 possible spatial locations (2 × 5 grid) in a touchscreen operant system. After a delay, animals were simultaneously presented with the original stimulus and a rewarded stimulus in a novel location ("choice phase"). PAE and saccharin (SAC) control mice were trained on a series of problems that systematically increased the difficulty by decreasing the separation between the sample and choice stimuli. Next, a separate cohort of PAE and SAC animals were given a brief training and then tested on a challenging variant where both the separation and delay varied with each trial. Results: We found that PAE mice were generally able to perform at levels similar to SAC control mice at progressively more difficult separations. When tested on the most difficult unpredictable variant immediately, PAE showed a sex‐specific deficit with PAE females performing worse during long delays. Conclusions: Taken together, these data demonstrate the utility of the TUNL task for examining PAE related alterations in hippocampal function and underline the need to examine sex‐by‐treatment interactions in these models. Abstract : Prenatally alcohol exposed mice tested on a touch‐screen delay non‐matching to location task were able to perform at control levels at progressively more difficult separations. When tested on a variant with unpredictable delays and separation immediately, exposed animals showed a sex specific deficit with PAE females performing worse during long delays. These results show the importance of training and testing order on operant tasks, and the need to examine sex and treatment effects and interactions in developmental exposure models.